2016
DOI: 10.1515/hukin-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vertical Jumps and Anthropometric Variables in Maximal Kicking Ball Velocities in Elite Soccer Players

Abstract: Kicking is one of the most important skills in soccer and the ability to achieve ma ximal kicking velocity with both legs leads to an advantage for the soccer player. This study examined the relationship be tween kicking ball velocity with both legs using anthropometric measurements and vertical jumps (a squat jump (SJ); a countermovement jump without (CMJ) and with the arm swing (CMJA) and a reactive jump (RJ)). Anthropome tric measurements did not correlate with kicking ball velocity. Vertical jumps correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
11
3
Order By: Relevance
“…In contrast to the preferred leg, the relationship between kicking velocity with the non-preferred leg and the vertical jump performance has received minimal research attention in the literature. To the best of our knowledge, only one study, conducted by our group, in elite adult players attempted to examine this relationship (Rodríguez-Lorenzo, et al, 2016), and found that this correlation was absent using exactly the same methodology as the present study. Nunome et al (2006) attributed the differences in kick biomechanics between the two limbs to the skill level of the players (Nunome et al 2006), i.e.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In contrast to the preferred leg, the relationship between kicking velocity with the non-preferred leg and the vertical jump performance has received minimal research attention in the literature. To the best of our knowledge, only one study, conducted by our group, in elite adult players attempted to examine this relationship (Rodríguez-Lorenzo, et al, 2016), and found that this correlation was absent using exactly the same methodology as the present study. Nunome et al (2006) attributed the differences in kick biomechanics between the two limbs to the skill level of the players (Nunome et al 2006), i.e.…”
Section: Discussionmentioning
confidence: 72%
“…The present findings seem to be consistent with another research conducted in young soccer players, which found that maximal kicking velocity was significantly correlated with body mass, height and body mass index (Bekris, et al, 2015;Brahim, Bougatfa, & Mohamed, 2013;Wong, et al, 2009). However, adult soccer players did not show any correlation between those parameters (Rodríguez-Lorenzo, et al, 2016). One possible explanation is that during the prepubertal and pubertal periods, transitory anthropometrical features associated with physical and maturity process, such as weight, height and strength (Figueiredo, Gonçalves, Coelho, Silva, & Malina, 2009;Malina, et al, 2000Malina, et al, , 2005Ré, Cattuzzo, Santos, & Monteiro, 2014) may have a high influence on the kicking performance.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations